EVOLUTION OF SCIENTIFIC APPROACHES TO THE ECONOMIC SECURITY - Maksymiuk , М. М. (The actual problems of regional economy development, 2016)
In the article analyzed the history of origin, evolution of the concept “economic security” and shown that forming of the scientific meaning of economic category passed a few stages. By means of historical method are distinguished basic events and periods of development of scientific thought about economic security, their reasons, pre-conditions and consequences. Analyzed the scientific developments sanctified to research of economic security on the different levels of economic system. Confirmed that economic security of national economy are the fundamental category in the system of economic security. JEL: H 56